2019
DOI: 10.1177/1740774519868310
|View full text |Cite
|
Sign up to set email alerts
|

Availability of study protocols for randomized trials published in high-impact medical journals: A cross-sectional analysis

Abstract: Background: To improve reporting transparency and research integrity, some journals have begun publishing study protocols and statistical analysis plans alongside trial publications. We sought to assess the overall availability and characteristics of protocols and statistical analysis plans of randomized clinical trials published in the top five (by impact factor) general medicine journals. Methods: All randomized clinical trials published in Annals of Internal Medicine, BMJ, JAMA, Lancet, and NEJM in 2016 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 31 publications
2
31
3
Order By: Relevance
“…Our results are broadly consistent with previous reviews. Spence et al [33] evaluated the availability of protocols and SAPs for trials published in high-impact medical journals and found similar rates of availability. However, the rates of discrepancies we found were generally lower than those previously reported [9,11,21,22].…”
Section: Discussionmentioning
confidence: 98%
“…Our results are broadly consistent with previous reviews. Spence et al [33] evaluated the availability of protocols and SAPs for trials published in high-impact medical journals and found similar rates of availability. However, the rates of discrepancies we found were generally lower than those previously reported [9,11,21,22].…”
Section: Discussionmentioning
confidence: 98%
“…We note that transparency around the statistical methods used in clinical trials is increasing, and there are initiatives in place to further increase transparency (for example, those conducted by the UKCRC CTU network, https://www.ukcrc-ctu.org.uk/). However, there is still a long way to go; evidence shows that the statistical methods for the trial's primary outcome are often poorly specified in both trial protocols [5,26,27] and Statistical Analysis Plans [26]; that protocols and Statistical Analysis Plans are often not made publicly available, or are only done so after they may have already been modified during the course of the trial [26,27,29]; that undisclosed changes to the planned analysis approach are frequent [2,26,27]; and that reporting around data access and blinding status of statisticians is often poor [26,27], hampering the ability of readers to evaluate whether changes have been made based on unblinded trial data. Pre-SPEC can play a part, alongside other initiatives, to help increase transparency in clinical trials, and resolving some of the issues outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are broadly consistent with previous reviews. Spence et al (30) evaluated the availability of protocols and SAPs for trials published in high impact medical journals, and found similar rates of availability. However, the rates of discrepancies we found were generally lower than those previously reported (8, 10, 20, 21).…”
Section: Discussionmentioning
confidence: 99%